Multilayer ceramic capacitor and method of manufacturing same

By using barium titanate-based main components and phosphorus elements in the dielectric layer of a multi-layer ceramic capacitor and adopting a specific manufacturing method, the problem of insufficient reliability and voltage resistance in high temperature and humidity environments is solved, and efficient high temperature and humidity resistance is achieved.

CN119852093APending Publication Date: 2025-04-18SAMSUNG ELECTRO MECHANICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410391242.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-10-18
Filing Date
2024-04-02
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

It is difficult for existing multi-layer ceramic capacitors to maintain excellent reliability and voltage resistance under high temperature and humidity environments.

Method used

By introducing barium titanate-based main component and phosphorus elements into the dielectric layer, combined with a specific manufacturing method, including mixing the powder of the barium (Ba) precursor and the titanium (Ti) precursor and the phosphorus (P)-containing compound, to form uniform dielectric grains to improve the high temperature and humidity resistance of the capacitor.

Benefits of technology

It realizes the high reliability and excellent voltage resistance characteristics of multi-layer ceramic capacitors in high temperature and humidity environments, and meets the high demands of automotive electronics and other applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119852093A_ABST
    Figure CN119852093A_ABST
Patent Text Reader

Abstract

Provided are a multilayer ceramic capacitor and a method of manufacturing the same, the multilayer ceramic capacitor including: a capacitor body including a dielectric layer and an inner electrode layer; and an external electrode disposed outside the capacitor body, in which the dielectric layer includes a barium titanate-based main component and a phosphorus (P) element, and includes the phosphorus (P) element in an amount of 0.006 to 0.23 mole parts based on 100 mole parts of the barium titanate-based main component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to a multilayer ceramic capacitor and a method of manufacturing the same. Background Art

[0002] Electronic components using ceramic materials include capacitors, inductors, piezoelectric elements, varistors, or thermistors. Among such ceramic electronic components, multilayer ceramic capacitors (MLCCs) are used in various electronic devices due to their small size, high capacity, and ease of mounting.

[0003] For example, multilayer ceramic capacitors can be used as chip capacitors mounted in boards of various electronic products (including imaging devices such as liquid crystal displays (LCDs), plasma display panels (PDPs), and organic light emitting diode (OLED) displays, computers, personal portable terminals, and smart phones) to charge or discharge.

[0004] In particular, the demand for MLCCs for vehicle applications is increasing due to the advancement of automotive electronic control technology, and with the development of miniaturization and high functionality of vehicle electronic devices, MLCCs are required to have high capacity, high temperature resistance characteristics, and moisture resistance characteristics. Summary of the invention

[0005] The present disclosure intends to provide a multilayer ceramic capacitor having excellent reliability (such as high temperature resistance and moisture resistance) and withstand voltage characteristics.

[0006] The present disclosure is intended to provide a method of manufacturing a multilayer ceramic capacitor.

[0007] An embodiment of the present disclosure provides a multilayer ceramic capacitor, comprising: a capacitor body, including a dielectric layer and an inner electrode layer; and an outer electrode, arranged on the outside of the capacitor body, wherein the dielectric layer includes a barium titanate-based main component and a phosphorus (P) element, and based on 100 molar parts of the barium titanate-based main component, includes 0.006 molar parts to 0.23 molar parts of the phosphorus (P) element.

[0008] The dielectric layer may include a plurality of dielectric grains, and the dielectric grains may include the barium titanate-based main component and a phosphorus (P) element.

[0009] The D10 diameter of the dielectric grains may be 100 nm to 140 nm.

[0010] The D50 diameter of the dielectric grains may be 150 nm to 250 nm.

[0011] The D90 diameter of the dielectric grains may be 300 nm to 420 nm.

[0012] The coefficient of variation of the size of the dielectric grains obtained from Formula 1 is 30% to 45%.

[0013] [Formula 1]

[0014] Dimensional variation coefficient (%) = [standard deviation (σ) of dimensions / average value] × 100%.

[0015] (In Formula 1, the standard deviation (σ) of a dimension is the square root of the mean of the squares of the deviations.)

[0016] The dielectric layer may further include a subcomponent, and the subcomponent may include at least one selected from the group consisting of dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), barium (Ba), silicon (Si), aluminum (Al), calcium (Ca), and combinations thereof.

[0017] Based on 100 mol parts of the barium titanate-based main component, the dielectric layer may include at least one selected from the group consisting of: 0.1 mol part to 1.0 mol part of dysprosium (Dy), 0.1 mol part to 1.0 mol part of terbium (Tb), 0.01 mol part to 0.5 mol part of manganese (Mn), 0.01 mol part to 0.5 mol part of vanadium (V), 0.5 mol part to 3.0 mol parts of barium (Ba), 0.5 mol part to 4.0 mol parts of silicon (Si), 0.1 mol part to 1.0 mol part of aluminum (Al), and 0.01 mol part to 1.0 mol part of calcium (Ca).

[0018] Another embodiment of the present disclosure provides a method for manufacturing a multilayer ceramic capacitor, including: manufacturing a dielectric powder by mixing a barium titanate-based main component powder including a barium (Ba) precursor and a titanium (Ti) precursor and a phosphorus (P)-containing compound; manufacturing a dielectric green sheet by using a dielectric slurry including the dielectric powder, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet stacking structure by stacking the dielectric green sheets on which the conductive paste layer is formed; manufacturing a capacitor body including a dielectric layer and an inner electrode layer by sintering the dielectric green sheet stacking structure; and forming an outer electrode on the capacitor body, wherein the phosphorus (P)-containing compound is mixed in an amount of 0.006 to 0.23 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, and the dielectric layer includes the barium titanate-based main component and the phosphorus (P) element.

[0019] The phosphorus (P) compound may include phosphorus pentoxide (P 2 O 5 ), phosphoric acid (H 3 PO 4 ), phosphorus oxychloride (POCl 3 ), at least one selected from the group consisting of phosphorus-containing hydrocarbons and combinations thereof.

[0020] The phosphorus-containing hydrocarbon compound may include at least one selected from the group consisting of a phosphate compound, a phosphite compound, a phosphonate compound, a phosphinate compound, and a combination thereof.

[0021] The manufacturing of dielectric powder may further include, after mixing the barium titanate-based main component powder with a phosphorus (P)-containing compound to prepare a mixture, drying and dry-grinding the mixture obtained by the mixing, and calcining the pulverized material obtained by the dry grinding. The manufacturing of dielectric powder may also include, after calcining the pulverized material, wet-grinding the calcined material obtained by the calcination, and drying and dry-grinding the pulverized material obtained by the wet grinding.

[0022] Calcination may be performed at a temperature of 800°C to 1000°C.

[0023] The dielectric slurry may further include a subcomponent powder, and the subcomponent powder may include a 2 O 3 ), terbium oxide (Tb 2 O 3 ), manganese oxide (MnO 2 ), vanadium oxide (V 2 O 5 ), barium carbonate (BaCO 3 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), calcium carbonate (CaCO 3 ) and at least one selected from the group consisting of ) and combinations thereof.

[0024] The sub-component powder may include at least one selected from the following group consisting of: dysprosium oxide (Dy) in an amount of 0.1 to 1.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 O 3 ), 0.1 mol to 1.0 mol of terbium oxide (Tb 2 O 3 ), 0.01 mol to 0.5 mol of manganese oxide (MnO 2 ), 0.01 to 0.5 mole parts of vanadium oxide (V 2 O 5 ), 0.5 to 3.0 mol parts of barium carbonate (BaCO 3 ), 0.5 to 4.0 mole parts of silicon dioxide (SiO 2 ), 0.1 mol to 1.0 mol of aluminum oxide (Al 2 O 3), and 0.01 to 1.0 mole parts of calcium carbonate (CaCO 3 ).

[0025] The multilayer ceramic capacitor according to the embodiment has a dielectric layer with a uniform grain size, thereby having excellent reliability such as high temperature resistance characteristics and moisture resistance characteristics and withstand voltage characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 A perspective view of a multilayer ceramic capacitor according to an embodiment is shown.

[0027] Figure 2 Shown along Figure 1 A cross-sectional view of the multilayer ceramic capacitor taken along line II'.

[0028] Figure 3 Shown along Figure 1 A cross-sectional view of the multilayer ceramic capacitor taken along line II-II'.

[0029] Figure 4 A schematic diagram of dielectric grains in a dielectric layer according to an embodiment is shown.

[0030] Figure 5 A process flow chart of a method of manufacturing a multilayer ceramic capacitor according to an embodiment is shown.

[0031] Figure 6 A process flow chart illustrating a process for manufacturing a dielectric powder in a method of manufacturing a multilayer ceramic capacitor according to an embodiment. DETAILED DESCRIPTION

[0032] The present disclosure will be described more fully hereinafter with reference to the accompanying drawings, in which embodiments of the present disclosure are shown. The drawings and description are to be considered illustrative rather than restrictive in nature, and the same reference numerals denote the same elements throughout the specification. In the drawings, some constituent elements are enlarged, omitted or briefly shown, and the sizes of the corresponding constituent elements do not reflect the actual sizes.

[0033] The accompanying drawings are provided only to facilitate understanding of the embodiments disclosed in this specification and should not be interpreted as limiting the spirit disclosed in this specification. It should be understood that the present invention includes all modifications, equivalents, and alternatives without departing from the scope and spirit of the present invention.

[0034] Terms including ordinal numbers such as first, second, etc. will only be used to describe various components and should not be construed as limiting these components. These terms are only used to distinguish one component from other components.

[0035] It will be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, it can be directly on the other element, or intervening elements may also be present. More specifically, when an element is referred to as being "directly on" another element, there are no intervening elements. The terms "on..." or "above..." refer to being located above or below a target portion, and do not necessarily mean being located on the upper side of the target portion based on the direction of gravity.

[0036] It will be further understood that the terms "include" or "have" used in this specification refer to the presence of stated features, numbers, steps, operations, components, parts or combinations thereof, but do not exclude the presence or addition of one or more other features, numbers, steps, operations, components, parts or combinations thereof. Unless explicitly described to the contrary, the word "include" and its variations (such as "comprising", "having") will be understood to imply the inclusion of the stated elements but not the exclusion of any other elements.

[0037] The phrase "in a plan view" means observing a target portion from the top, and the phrase "in a cross-sectional view" means observing a cross section vertically cutting the target portion from the side.

[0038] When a component is described as being “connected (contacted, coupled)” to another component, the component may be “directly connected” to the other component, may be “connected” to the other component through a third component, or may be physically or electrically connected to the other component, and they may be represented by different names according to position or function, but they may be substantially integrated into one body.

[0039] Now refer to Figures 1 to 3 A multilayer ceramic capacitor according to an embodiment is described.

[0040] Figure 1 shows a perspective view of a multilayer ceramic capacitor according to an embodiment, Figure 2 Shown along Figure 1 A cross-sectional view of a multilayer ceramic capacitor taken along line II', and Figure 3 Shown along Figure 1 A cross-sectional view of the multilayer ceramic capacitor taken along line II-II'.

[0041] Figures 1 to 3The L-axis, W-axis, and T-axis shown in the figure represent the length direction, width direction, and thickness direction of the capacitor body 110, respectively. Here, the thickness direction (T-axis direction) may be a direction perpendicular to the wide surface (main surface) of the sheet-like constituent element, and may be used, for example, as the same concept as the direction in which the multilayer dielectric layer 111 is stacked. The length direction (L-axis direction) may be a direction extending in parallel to the wide surface (main surface) of the sheet-like constituent element, and may be a direction substantially perpendicular to the thickness direction (T-axis direction), for example, may be a direction along which the first external electrode 131 and the second external electrode 132 are relative to each other. The width direction (W-axis direction) may be a direction extending in parallel to the wide surface (main surface) of the sheet-like constituent element, and may be a direction substantially perpendicular to the thickness direction (T-axis direction) and the length direction (L-axis direction), and the length of the sheet-like constituent element in the length direction (L-axis direction) may be greater than the length in the width direction (W-axis direction).

[0042] Reference Figures 1 to 3 , the multilayer ceramic capacitor 100 according to the embodiment includes a capacitor body 110 and external electrodes 131 and 132 disposed outside the capacitor body 110. The external electrodes 131 and 132 may include a first external electrode 131 and a second external electrode 132 disposed at respective opposite ends in a length direction (L-axis direction) of the capacitor body 110.

[0043] As an example, the capacitor body 110 may have an approximately hexahedral shape.

[0044] For better understanding and ease of description of the embodiments, the two sides of the capacitor body 110 opposite to each other in the thickness direction (T-axis direction) will be defined as a first side and a second side, the two sides connected to the first side and the second side and opposite to each other in the length direction (L-axis direction) will be defined as a third side and a fourth side, and the two sides connected to the first side and the second side, connected to the third side and the fourth side and opposite to each other in the width direction (W-axis direction) will be defined as a fifth side and a sixth side.

[0045] For example, the first side as the lower surface may be a side facing the installation direction. In addition, the first side to the sixth side may be flat, and the embodiment is not limited thereto. For example, the first side to the sixth side may be a curved surface, the central portion of which is convex, and the edges as the boundaries of the corresponding sides may be rounded.

[0046] The shape and size of the capacitor body 110 and the number of layers of the dielectric layer 111 are not limited to those shown in the drawings of the present embodiment.

[0047] The capacitor body 110 includes a dielectric layer 111 and internal electrode layers 121 and 122. Specifically, the capacitor body 110 includes a dielectric layer 111 and first and second internal electrodes 121 and 122 alternately arranged in a thickness direction (T-axis direction) with the dielectric layer 111 interposed therebetween.

[0048] Adjacent dielectric layers 111 of the capacitor body 110 may be integrated to such an extent that it is difficult to inspect a boundary therebetween without using a scanning electron microscope (SEM).

[0049] The capacitor body 110 may have an effective portion. The effective portion is a region where the dielectric layer 111 and the internal electrode layers 121 and 122 are alternately arranged, and is a portion that contributes to forming the capacitance of the multilayer ceramic capacitor 100. Specifically, the effective portion may be a region where the first internal electrode 121 and the second internal electrode 122 stacked in the thickness direction (T-axis direction) overlap.

[0050] In addition, the capacitor body 110 may further include a cover portion and a side edge portion.

[0051] The covering portion may be an edge portion in the thickness direction and may be disposed on the upper and lower sides of the effective portion in the thickness direction (T-axis direction). The covering portion may be a single dielectric layer 111 or two or more dielectric layers 111 stacked on the upper and lower sides of the effective portion, respectively.

[0052] The side edge portions may be side covering portions, and may be provided on respective sides of the effective portion that are opposite to each other in the width direction (W-axis direction), that is, on the fifth side and the sixth side. The side edge portions may be formed by coating the conductive paste layer in a predetermined region of the surface of the dielectric green sheet when the conductive paste layer for the internal electrode layer is coated on the surface of the dielectric green sheet, stacking dielectric green sheets on which the conductive paste layer is not coated on respective lateral sides (e.g., both sides in the W-axis direction) of the surface of the dielectric green sheet, and sintering them, but is not limited to this forming method.

[0053] The covering portion and the side margin portion serve to prevent damage to the first and second internal electrodes 121 and 122 due to physical stress or chemical stress.

[0054] The dielectric layer 111 includes a barium titanate-based main component and phosphorus (P) element.

[0055] The barium titanate-based main component is a dielectric matrix material having a high dielectric constant, and contributes to forming the dielectric constant of the multilayer ceramic capacitor 100 .

[0056] The barium titanate-based main component may include, for example, BaTiO 3 、Ba(Ti,Zr)O 3 、Ba(Ti,Sn)O3 、(Ba,Ca)TiO 3 、(Ba,Ca)(Ti,Zr)O 3 、(Ba,Ca)(Ti,Sn)O 3 、(Ba,Sr)TiO 3 、(Ba,Sr)(Ti,Zr)O 3 、(Ba,Sr)(Ti,Sn)O 3 and at least one selected from the group consisting of and combinations thereof.

[0057] The phosphorus (P) element may be derived from a phosphorus (P)-containing compound added to the dielectric matrix material.

[0058] Based on 100 parts by mole of the barium titanate-based main component, the amount of the phosphorus (P) element included may be 0.006 parts by mole to 0.23 parts by mole, and may be, for example, 0.01 parts by mole to 0.15 parts by mole. When the phosphorus (P) element included in the dielectric layer 111 is within this range, the abnormal grain growth of the dielectric grains can be suppressed by the difference in the ion radius of the phosphorus (P) element, and thus the dielectric grains of uniform size in the dielectric layer can be ensured. Therefore, the reliability (such as high temperature resistance and moisture resistance) and the withstand voltage characteristics of the multilayer ceramic capacitor can be improved.

[0059] The content of phosphorus (P) element in the dielectric layer 111 can be measured by inductively coupled plasma (ICP) analysis. In detail, the content of phosphorus (P) element in the dielectric layer sample of the multilayer ceramic capacitor can be measured in a quartz chamber by using an AVIO500 (Perkin Elmer) device of an inductively coupled plasma-optical emission spectrometer (ICP-OES) under conditions such as a plasma gas flow rate of 12 L / min, an auxiliary gas flow rate of 0.2 L / min, a nebulizer flow rate of 0.5 L / min, a plasma RF power of 1400 W, and an axial plasma mode.

[0060] The dielectric layer 111 may include a plurality of dielectric grains. In this case, the dielectric grains may include the above-mentioned barium titanate-based main component and phosphorus (P) element.

[0061] The D10 diameter of the dielectric grains may be 100 nm to 140 nm, for example, 110 nm to 130 nm. In addition, the D50 diameter of the dielectric grains may be 150 nm to 250 nm, for example, 180 nm to 220 nm, or for example, 190 nm to 210 nm. In addition, the D90 diameter of the dielectric grains may be 300 nm to 420 nm, for example, 310 nm to 350 nm, or for example, 320 nm to 340 nm. When the sizes of the individual dielectric grains (i.e., D10, D50, and D90) are within this range, high reliability and excellent withstand voltage characteristics may be achieved by ensuring that the dielectric layer has uniform dielectric grains.

[0062] The size of dielectric grains can be measured by the following method.

[0063] First, the multilayer ceramic capacitor 100 is placed in an epoxy resin mixed solution and cured, and one side (WT side) of the capacitor body 110 in the W-axis direction and the T-axis direction is polished to 1 / 2 point in the L-axis direction to obtain a cross-sectional sample, and the cross-sectional sample is fixed in a chamber and maintained under a vacuum atmosphere, and the effective part including the dielectric layer 111 and the inner electrode layers 121 and 122 is observed. Next, the effective part of the cross-sectional sample can be ion milled, and a scanning electron microscope (SEM) can be used for measurement. For example, the scanning electron microscope uses the Verios G4 product from Thermofisher Scientific, the measurement conditions are 10kV, 0.2nA, the analysis magnification can be 100 times, and at least one layer, at least three layers, at least five layers, and at least ten layers of the dielectric layer 111 can be measured. Regarding the size of the dielectric grains, a size distribution cumulative curve is generated by measuring the maximum long axis of at least 100 dielectric grains in the scanning electron microscope image of the cross-sectional sample, and the D10 diameter, D50 diameter, and D90 diameter are calculated respectively. In this case, the D10 diameter, the D50 diameter, and the D90 diameter respectively represent the sizes at the 10%, 50%, and 90% points in the cumulative curve of the size distribution.

[0064] In addition, the coefficient of variation of the size of the dielectric grains may be 30% to 45%, for example, 30% to 43%. When the coefficient of variation of the size of the dielectric grains is within this range, the size distribution characteristics of the dielectric grains are excellent, thereby ensuring a multilayer ceramic capacitor having excellent reliability (such as high temperature resistance and moisture resistance) and withstand voltage characteristics.

[0065] The size variation coefficient of dielectric grains can be obtained by Equation 1.

[0066] [Formula 1]

[0067] Coefficient of dimensional variation (%) = [standard deviation of dimension (σ) / average value] × 100%

[0068] In Formula 1, the standard deviation (σ) of a dimension means squared deviations, summed and divided by the number of measurements, and taking the square root, i.e., the square root of the average of the squares of the deviations (differences between individual measurements and the average) as in Formula 2.

[0069] [Formula 2]

[0070]

[0071] Figure 4 A schematic diagram of dielectric grains in a dielectric layer according to an embodiment is shown.

[0072] Reference Figure 4 , the dielectric layer 111 may include dielectric grains 10 and grain boundaries 20 between adjacent dielectric grains 10. At least one of the dielectric grains 10 may have a core-shell structure including a core 10a and a shell 10b surrounding the core 10a. The dielectric layer 111 including the phosphorus (P) element in an amount of 0.006 to 0.23 parts by mole relative to 100 parts by mole of the barium titanate-based main component may have a thickness of 1.1 to 1.1 mm. Figure 4 The dielectric grains 10 are shown to have uniform size.

[0073] The dielectric layer 111 may further include at least one selected from the group consisting of dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), barium (Ba), silicon (Si), aluminum (Al), calcium (Ca), and combinations thereof as a subcomponent.

[0074] The accessory component may originate from a metal oxide added as an accessory component to the dielectric matrix material.

[0075] Based on 100 molar parts of the barium titanate-based main component, dysprosium (Dy) in an amount of 0.1 to 1.0 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, terbium (Tb) in an amount of 0.1 to 1.0 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, manganese (Mn) in an amount of 0.01 to 0.5 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, vanadium (V) in an amount of 0.01 to 0.5 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, barium (Ba) in an amount of 0.5 to 3.0 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, silicon (Si) in an amount of 0.5 to 4.0 molar parts may be included. Based on 100 molar parts of the barium titanate-based main component, aluminum (Al) in an amount of 0.1 to 1.0 molar parts may be included. Calcium (Ca) may be included in an amount of 0.01 to 1.0 mol parts based on 100 mol parts of the barium titanate-based main component. When the auxiliary component is included within this content range, a multilayer ceramic capacitor having high capacity, high reliability, and excellent withstand voltage characteristics may be ensured.

[0076] The average thickness (average length in the T-axis direction) of the dielectric layer 111 may be 2.0 μm to 8.0 μm, for example, 2.4 μm to 7.8 μm. When the average thickness of the dielectric layer 111 is within this range, the reliability of the multilayer ceramic capacitor is excellent.

[0077] The average thickness of the dielectric layer 111 can be measured by placing the multilayer ceramic capacitor 100 in an epoxy resin mixed solution, curing it, polishing, ion milling, and analyzing it with a scanning electron microscope (SEM). For example, the scanning electron microscope uses the Verios G4 product from Thermofisher Scientific, the measurement conditions are 10kV, 0.2nA, the analysis magnification can be 100 times, and at least one layer, at least three layers, at least five layers, and at least ten layers of the dielectric layer 111 can be measured. In the scanning electron microscope (SEM) image, when the center point in the length direction (L axis direction) or the width direction (W axis direction) of the dielectric layer 111 is used as a reference point, the average thickness of the dielectric layer 111 can be the arithmetic mean of the thickness of the dielectric layer 111 at ten points away from the reference point at a predetermined interval. The interval of the ten points can be adjusted according to the scale of the scanning electron microscope (SEM) image, for example, the interval can be 1μm to 100μm, 1μm to 50μm, or 1μm to 10μm. At this time, ten points must be disposed in the dielectric layer 111, and when the ten points are not disposed in the dielectric layer 111, the position of the reference point may be changed or the intervals between the ten points may be adjusted.

[0078] The first inner electrode 121 and the second inner electrode 122 have different polarities and are alternately arranged to be opposite to each other in the T-axis direction with the dielectric layer 111 interposed between the first inner electrode 121 and the second inner electrode 122, and one end of the first inner electrode 121 and one end of the second inner electrode 122 can be exposed through the third side and the fourth side of the capacitor body 110, respectively.

[0079] The first and second internal electrodes 121 and 122 may be electrically insulated from each other by a dielectric layer 111 disposed in between.

[0080] Ends of the first and second internal electrodes 121 and 122 alternately exposed through the third and fourth sides of the capacitor body 110 may be electrically connected to the first and second external electrodes 131 and 132 , respectively.

[0081] The first and second internal electrodes 121 and 122 include a conductive metal, for example, a metal such as Ni, Cu, Ag, Pd, and Au, or an alloy thereof such as an Ag—Pd alloy.

[0082] The first and second internal electrodes 121 and 122 may include dielectric particles having the same composition as that of the ceramic material included in the dielectric layer 111 .

[0083] The first and second internal electrodes 121 and 122 may be formed by using a conductive paste including a conductive metal. A method for printing the conductive paste may use a screen printing method or a gravure printing method.

[0084] The average thickness of the first and second internal electrodes 121 and 122 may be 0.1 μm to 2 μm. The average thickness of the first and second internal electrodes 121 and 122 may be measured by scanning electron microscope (SEM) analysis. Here, the scanning electron microscope (SEM) analysis corresponds to a method for measuring the average thickness of the above-mentioned dielectric layer 111, and thus will not be described.

[0085] The capacitor body 110 may be formed by sintering a multilayer body in which the dielectric layer 111 and the internal electrode layers 121 and 122 are stacked.

[0086] The first and second external electrodes 131 and 132 provide voltages having different polarities and may be electrically connected to exposed portions of the first and second internal electrodes 121 and 122 , respectively.

[0087] According to the above configuration, when a predetermined voltage is applied to the first external electrode 131 and the second external electrode 132, charges are stored between the first internal electrode 121 and the second internal electrode 122 facing each other. In this case, the capacitance of the multilayer ceramic capacitor 100 is proportional to the area of ​​overlap of the first internal electrode 121 and the second internal electrode 122 in the T-axis direction in the effective portion.

[0088] The first external electrode 131 and the second external electrode 132 may respectively include a first access portion and a second access portion and a first band portion and a second band portion, the first access portion and the second access portion are respectively arranged on the third side and the fourth side of the capacitor body 110 and are respectively connected to the first internal electrode 121 and the second internal electrode 122, the first band portion is arranged at the corner where the third side of the capacitor body 110 intersects with the first side and the second side or at the corner where the third side intersects with the fifth side and the sixth side, and the second band portion is arranged at the corner where the fourth side of the capacitor body 110 intersects with the first side and the second side or at the corner where the fourth side intersects with the fifth side and the sixth side.

[0089] The first and second band portions may extend from the first and second access portions to a portion of at least one of the first, second, fifth, and sixth sides of the capacitor body 110 , respectively. The first and second band portions may improve the fixing strength of the first and second external electrodes 131 and 132 .

[0090] The first and second external electrodes 131 and 132 may include a sintered metal film contacting the capacitor body 110 , a conductive resin layer disposed to cover the sintered metal film, and a plating layer for covering the conductive resin layer.

[0091] The sintered metal film may include conductive metal and glass.

[0092] The conductive metal may include at least one selected from the group consisting of copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), alloys thereof, and combinations thereof. For example, the conductive metal including copper (Cu) may mean that the conductive metal includes single substance copper (Cu) or includes a copper (Cu) alloy. When the conductive metal includes copper, for 100 molar parts of copper (Cu), less than or equal to 5 molar parts of metal other than copper (Cu) may be included.

[0093] The glass may include a composition including an oxide, for example, the oxide may be at least one selected from the group consisting of silicon oxide, boron oxide, aluminum oxide, transition metal oxide, alkali metal oxide, and alkaline earth metal oxide. The transition metal may include at least one selected from zinc (Zn), titanium (Ti), copper (Cu), vanadium (V), manganese (Mn), iron (Fe), and nickel (Ni). The alkali metal may include at least one selected from the group consisting of lithium (Li), sodium (Na), and potassium (K), and the alkaline earth metal may be one or more selected from magnesium (Mg), calcium (Ca), strontium (Sr), and barium (Ba).

[0094] Alternatively, the conductive resin layer may be formed on the sintered metal film, for example, the conductive resin layer may completely cover the sintered metal film. In addition, the first and second external electrodes 131 and 132 may not include the sintered metal film, in which case the conductive resin layer may directly contact the capacitor body 110.

[0095] The conductive resin layer may extend to the first and second sides or the fifth and sixth sides of the capacitor body 110, and the length of the region (i.e., the band portion) where the conductive resin layer extends to the first and second sides or the fifth and sixth sides of the capacitor body 110 may be greater than the length of the region (i.e., the band portion) where the sintered metal film extends to the first and second sides or the fifth and sixth sides of the capacitor body 110. In other words, the conductive resin layer is formed on the sintered metal film and may completely cover the sintered metal film.

[0096] The conductive resin layer may include resin and conductive metal.

[0097] The resin included in the conductive resin layer is not particularly limited as long as it has adhesion and impact absorption and can be mixed with the conductive metal powder to make a paste, for example, the resin may include phenolic resin, acrylic resin, silicone resin, epoxy resin or polyimide resin.

[0098] The conductive metal included in the conductive resin layer may be used for electrical connection to the first and second internal electrodes 121 and 122 or the sintered metal film.

[0099] The conductive metal included in the conductive resin layer may have a spherical shape, a flake shape, or a combination thereof. In other words, the conductive metal may be formed in a flake shape, a spherical shape, or may be a mixture of a flake shape and a spherical shape.

[0100] Here, the spherical shape may include a shape that is not a perfect sphere, for example, the spherical shape may include a shape in which the length ratio of the major axis to the minor axis (major axis / minor axis) is 1.45 or less. The flake shape refers to a flat and elongated shape, and is not particularly limited, for example, the length ratio of the major axis to the minor axis (major axis / minor axis) may be greater than or equal to 1.95.

[0101] The first and second external electrodes 131 and 132 may further include a plating layer disposed outside the conductive resin layer.

[0102] The plating layer may include at least one selected from the group consisting of nickel (Ni), copper (Cu), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), lead (Pb) and alloys thereof. For example, the plating layer may include a nickel (Ni) plating layer or a tin (Sn) plating layer, may have a form in which a nickel (Ni) plating layer and a tin (Sn) plating layer are stacked in sequence, or may have a form in which a tin (Sn) plating layer, a nickel (Ni) plating layer and a tin (Sn) plating layer are stacked in sequence. In addition, the plating layer may include a nickel (Ni) plating layer and / or a tin (Sn) plating layer.

[0103] The plating layer may improve the mountability, structural reliability, exterior durability, heat resistance, and equivalent series resistance (ESR) of the multilayer capacitor 100 on a substrate.

[0104] Now refer to Figure 5 and Figure 6 A method of manufacturing the multilayer ceramic capacitor 100 according to an embodiment is described.

[0105] Figure 5 A process flow chart of a method for manufacturing a multilayer ceramic capacitor according to an embodiment is shown, and Figure 6 A process flow chart illustrating a process for manufacturing a dielectric powder in a method of manufacturing a multilayer ceramic capacitor according to an embodiment.

[0106] Reference Figure 5, a method for manufacturing a multilayer ceramic capacitor includes: manufacturing a dielectric powder by mixing a barium titanate-based main component powder including a barium (Ba) precursor and a titanium (Ti) precursor and a phosphorus (P)-containing compound (S10); manufacturing a dielectric green sheet by using a dielectric slurry including the dielectric powder, and forming a conductive paste layer on a surface of the dielectric green sheet (S20); manufacturing a dielectric green sheet stacking structure by stacking the dielectric green sheets on which the conductive paste layer is formed (S30); manufacturing a capacitor body including a dielectric layer and an inner electrode layer by sintering the dielectric green sheet stacking structure (S40); and forming an outer electrode on the capacitor body (S50).

[0107] The process for manufacturing the dielectric powder ( S10 ) will now be described.

[0108] The dielectric powder may be manufactured by mixing a barium titanate-based main component powder and a phosphorus (P)-containing compound. The barium titanate-based main component powder may include a barium (Ba) precursor and a titanium (Ti) precursor.

[0109] The barium (Ba) precursor may include BaO 2 、BaTiO 3 、BaCO 3 At least one selected from the group consisting of BaO, BaO and a combination thereof.

[0110] The titanium (Ti) precursor may include titanium oxide, titanium salt or titanium alkoxide. The titanium (Ti) precursor may include, for example, at least one selected from the group consisting of titanium dioxide, titanium diisopropyl diacetylacetonate (TPA), titanium alkoxide and combinations thereof.

[0111] The barium (Ba) precursor may be included in an amount of 0.990 to 1.000 parts by mole based on 1 part by mole of the titanium (Ti) precursor.

[0112] Based on 100 molar parts of the barium titanate-based main component powder, a phosphorus (P) compound can be mixed in an amount of 0.006 molar parts to 0.23 molar parts, for example, 0.01 molar parts to 0.15 molar parts of the phosphorus (P) compound can be mixed. When the phosphorus (P) compound is mixed within this content range in the case of manufacturing a dielectric powder, a uniform barium titanate-based powder can be obtained, so that dielectric grains with uniform sizes can be obtained in the dielectric layer. Therefore, a multilayer ceramic capacitor with excellent reliability (such as high temperature resistance and moisture resistance) and withstand voltage characteristics can be obtained.

[0113] The phosphorus (P)-containing compound may include, for example, phosphorus pentoxide (P 2 O 5 ), phosphoric acid (H 3 PO 4 ), phosphorus oxychloride (POCl 3), at least one selected from the group consisting of hydrocarbons containing phosphorus (P) and combinations thereof, but not limited thereto.

[0114] The phosphorus-containing hydrocarbon compound may include at least one selected from the group consisting of a phosphate compound, a phosphite compound, a phosphonate compound, a phosphinate compound, and a combination thereof.

[0115] Reference Figure 6 , manufacturing the dielectric powder (S10) may include: mixing a barium titanate-based main component powder including a barium (Ba) precursor and a titanium (Ti) precursor with a phosphorus (P)-containing compound (S11); drying and dry-grinding the mixture obtained by the mixing (S12); and calcining the crushed material obtained by the dry grinding (S13). Optionally, manufacturing the dielectric powder (S10) may further include wet-grinding the calcined material obtained by the calcination after step S13 (S14). Optionally, manufacturing the dielectric powder (S10) may further include drying and dry-grinding the crushed material obtained by the wet grinding after step S14 (S15).

[0116] Mixing (S11) may include wet mixing. Specifically, wet mixing may be performed using a disperser such as a bead mill or a ball mill, or a high pressure dispersion process may be performed to disperse the mixture in a wet manner together with a solvent. For example, in the case of using a bead mill for dispersion, beads having a diameter of about 0.03 mm to about 0.1 mm may be used for a dispersion process of about 5 to about 30 times at a circumferential speed of about 5 m / s to about 15 m / s.

[0117] The solvent used for wet mixing may include, for example, an aqueous solvent such as ion-exchanged water, pure water, ultrapure water, or distilled water, or an alcohol solvent or an amine solvent such as ammonia or an organic amine that can be used together with water.

[0118] Optionally, a dispersant may be further added in the mixing (S11), and the dispersant may include, for example, polyvinyl butyl-based dispersants, polyvinyl acetal-based dispersants, polycarbonate-based dispersants, maleic acid-based dispersants, polyethylene glycol-based dispersants, allyl ether copolymer-based dispersants, and the like.

[0119] Alternatively, the mixture obtained by the mixing may be dried and dry-milled ( S12 ).

[0120] A process of calcining the pulverized material obtained by dry grinding is performed (S13).

[0121] Calcination can be carried out at a temperature of 800° C. to 1000° C., for example, 840° C. to 900° C. Calcination can be carried out for 1 hour to 8 hours, for example, 2 hours to 6 hours. Calcination can be carried out in a vacuum atmosphere or a normal pressure atmosphere, for example, in an atmosphere of 10000 Pa to 1000000 Pa. The vacuum atmosphere can be, for example, a vacuum atmosphere of less than or equal to about 20000 Pa, or less than or equal to about 100 Pa. When calcination is carried out under conditions including this temperature range, a uniform dielectric powder can be obtained without non-reaction and dispersion problems.

[0122] Optionally, the calcined material obtained by the calcination is wet-milled ( S14 ), and optionally, the pulverized material obtained by the wet milling is dried and dry-milled ( S15 ) to obtain a dielectric powder.

[0123] A dielectric green sheet is formed by using a dielectric slurry including the obtained dielectric powder, and a conductive paste layer is formed on the dielectric green sheet (S20).

[0124] The dielectric slurry may further include a subsidiary component powder. The subsidiary component powder may be used in a sol type dispersed in an organic solvent.

[0125] The auxiliary component powder may include dysprosium oxide (Dy 2 O 3 ), terbium oxide (Tb 2 O 3 ), manganese oxide (MnO 2 ), vanadium oxide (V 2 O 5 ), barium carbonate (BaCO 3 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ), calcium carbonate (CaCO 3 ) and at least one selected from the group consisting of a combination thereof. The auxiliary component powder may be used in a sol form dispersed in an organic solvent.

[0126] The dysprosium oxide (Dy) may be included in an amount of 0.1 to 1.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 O 3 The terbium oxide (Tb) may be included in an amount of 0.1 to 1.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 O 3 The manganese oxide (MnO) may be included in an amount of 0.01 to 0.5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 The vanadium oxide (V) may be included in an amount of 0.01 to 0.5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2O 5 The barium carbonate (BaCO) may be included in an amount of 0.5 to 3.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 3 The silicon dioxide (SiO2) may be included in an amount of 0.5 to 4.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 The aluminum oxide (Al2O3) may be included in an amount of 0.1 to 1.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 2 O 3 The calcium carbonate (CaCO) may be included in an amount of 0.01 to 1.0 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. 3 ). When the auxiliary component is included in this content range, a multilayer ceramic capacitor having high capacity, high reliability and excellent withstand voltage characteristics can be ensured. The content of the auxiliary component / auxiliary component powder may be based on the content of the corresponding element included in the auxiliary component without distinguishing the form of additives such as oxides or carbonates. For example, the above-mentioned 0.1 mol part to 1.0 mol part of dysprosium oxide (Dy 2 O 3 ) can be based on the inclusion of dysprosium oxide (Dy 2 O 3 ) is the amount of Dy element in .

[0127] Furthermore, the dielectric slurry may be manufactured by further mixing an additive such as a dispersant, a binder, a plasticizer, a lubricant, or an antistatic agent and a solvent.

[0128] The dispersant may include, for example, at least one selected from the group consisting of a phosphate dispersant, a polycarboxylic acid dispersant, and a combination thereof. Based on 100 parts by weight of the dielectric powder, the dispersant may be mixed in an amount of 0.1 to 5 parts by weight, for example, 0.3 to 3 parts by weight. When the dispersant is mixed within this content range, the dispersion of the dielectric slurry may be excellent, and the amount of impurities included in the manufactured dielectric layer may be reduced.

[0129] The binder may be, for example, an acrylic resin, a polyvinyl butyral resin, a polyvinyl acetal resin, and an ethyl cellulose resin. The binder may be added in an amount of 0.1 to 50 parts by weight, for example, 3 to 30 parts by weight, based on 100 parts by weight of the dielectric powder. When the binder is mixed within this content range, the dispersion of the dielectric slurry may be excellent, and the amount of impurities included in the manufactured dielectric layer may be reduced.

[0130] The plasticizer may include, for example, at least one selected from the group consisting of: phthalate compounds such as dioctyl phthalate, benzyl butyl phthalate, dibutyl phthalate, dihexyl phthalate, di(2-ethylhexyl)phthalate, or di(2-ethylbutyl)phthalate; adipate compounds such as dihexyl adipate or di(2-ethylhexyl) adipate; glycol compounds such as ethylene glycol, diethylene glycol, or triethylene glycol; and glycol ester compounds such as triethylene glycol dibutyrate, triethylene glycol di(2-ethyldibutyrate), or triethylene glycol di(2-ethylhexanoate). The plasticizer may be added in an amount of 0.1 to 20 parts by weight, for example, 1 to 10 parts by weight, based on 100 parts by weight of the dielectric powder. When the plasticizer is mixed within this content range, the dispersibility of the dielectric slurry is excellent, and the amount of impurities included in the manufactured dielectric layer may be reduced.

[0131] The solvent may include: an aqueous solvent such as water; an alcohol solvent such as ethanol, methanol, benzyl alcohol and methoxyethanol; an ethylene glycol solvent such as ethylene glycol and diethylene glycol; a ketone solvent such as acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone; an ester solvent such as butyl acetate, ethyl acetate, carbitol acetate and butyl carbitol acetate; an ether solvent such as methyl cellosolve, ethyl cellosolve, butyl ether and tetrahydrofuran; and an aromatic solvent such as benzene, toluene or xylene. Considering the solubility and dispersibility of various additives included in the dielectric slurry, the solvent may include an alcohol solvent or an aromatic solvent. Based on 100 parts by weight of the dielectric powder, the solvent may be mixed in an amount of 50 parts by weight to 1000 parts by weight, for example, in an amount of 100 parts by weight to 500 parts by weight. When the solvent is mixed within this content range, the dielectric slurry components can be fully mixed, and the solvent can be easily removed thereafter.

[0132] The mixing of the dielectric powder and the auxiliary component powder can be accomplished using a wet ball mill or a stirred mill. When zirconia balls are used in a wet ball mill, zirconia balls having a diameter of 0.1 mm to 10 mm can be used for wet mixing for 8 to 48 hours, or 10 hours or 24 hours.

[0133] The manufactured dielectric slurry is formed into a dielectric layer after firing.

[0134] A dielectric green sheet is manufactured using the dielectric slurry, and a conductive paste layer is formed on a surface of the dielectric green sheet (S20).

[0135] Methods for molding the produced dielectric slurry into a sheet shape include a belt molding method such as a doctor blade method and a calendar roll method, for example, a roll-on molding coater of a head discharge method may be used, and then a dielectric green sheet may be obtained by drying the molded body.

[0136] In order to form a conductive paste layer that becomes an inner electrode layer after sintering, the conductive paste can be manufactured by mixing a conductive powder made of a conductive metal or an alloy thereof, a binder and a solvent. In addition, if necessary, barium titanate powder as a common material can be mixed together. The common material can inhibit the sintering of the conductive powder during the sintering process. The conductive paste is applied to the surface of the dielectric green sheet in a predetermined pattern using various printing methods (such as screen printing or transfer printing) to form a conductive paste layer.

[0137] A dielectric green sheet stack structure is manufactured by stacking dielectric green sheets having internal electrode patterns formed thereon and pressing the dielectric green sheets in a stacking direction (S30). At this time, the dielectric green sheets and the internal electrode patterns may be stacked so that the dielectric green sheets are disposed on the upper and lower surfaces of the dielectric green sheet stack structure in the stacking direction.

[0138] The manufactured dielectric green sheet stack structure may be cut into a predetermined size by dicing or the like.

[0139] In addition, as needed, the dielectric green sheet stack structure may be cured and dried to remove the plasticizer, etc., and then it may be drum polished using a horizontal centrifugal drum machine, etc. Regarding drum polishing, the dielectric green sheet stack structure may be placed in a drum container together with a medium and a polishing liquid, and unnecessary portions such as burrs generated during cutting may be polished by applying a rotational motion or vibration to the drum container. In addition, after drum polishing, the dielectric green sheet stack structure may be washed with a cleaning solution such as water and dried.

[0140] The capacitor body is manufactured by removing the binder from the dielectric green sheet stack structure and sintering it (S40).

[0141] The conditions for removing the binder may be appropriately adjusted according to the components of the dielectric layer and the inner electrode layer. For example, the temperature during the binder removal process may be increased at a rate of 5°C / hour to 300°C / hour, the carrier temperature may be 180°C to 400°C, and the temperature maintenance time may be 0.5 hours to 24 hours. The atmosphere during the binder removal process may be air or a reducing atmosphere.

[0142] The conditions of the sintering process may be appropriately adjusted according to the main component composition of the dielectric layer or the main component composition of the inner electrode. For example, the sintering may be performed at a temperature of 1100° C. to 1400° C., for example, 1200° C. to 1350° C. In addition, the sintering may be performed for 0.5 hours to 8 hours, for example, 1 hour to 3 hours. In addition, the sintering may be performed in a reducing atmosphere, for example, in a humidified mixed gas atmosphere of nitrogen and hydrogen. When the inner electrode includes nickel (Ni) or an alloy of nickel (Ni), the oxygen partial pressure in the sintering atmosphere may be 1.0×10 -14 MPa to 1.0×10 -10 MPa.

[0143] Annealing may be performed after sintering as needed. Annealing reoxidizes the dielectric layer and may be performed while sintering is performed in a reducing atmosphere. The conditions of the annealing process may also be appropriately adjusted according to the composition of the dielectric layer. For example, the temperature during annealing may be 950°C to 1150°C, the duration of annealing may be 0 hours to 20 hours, and the temperature may be increased at a rate of 50°C / hour to 500°C / hour. The annealing atmosphere may be humidified nitrogen (N 2 ) atmosphere, and the oxygen partial pressure may be 1.0×10 -9 MPa to 1.0×10 -5 MPa.

[0144] Regarding the binder removal process, sintering process or annealing process, for example, a wetting agent may be used to humidify nitrogen or mixed gas, etc., in which case the temperature of the wetting agent may be 5° C. to 75° C. The binder removal process, sintering process and annealing process may be performed continuously or independently.

[0145] Alternatively, surface processing such as sandblasting, laser irradiation, and barrel polishing may be performed on the third and fourth sides of the manufactured capacitor body 110. By performing the surface processing, the end of the first inner electrode and the end of the second inner electrode may be exposed on the outermost surface of the third side and the outermost surface of the fourth side, respectively, so that the electrical bonding between the first outer electrode and the first inner electrode and between the second outer electrode and the second inner electrode becomes better, and an alloy may be easily formed.

[0146] An external electrode is formed on one side of the manufactured capacitor body 110 ( S50 ).

[0147] For example, a paste for forming a sintered metal film may be applied to the external electrodes, and may be sintered to form the sintered metal film.

[0148] The paste for forming the sintered metal film may include conductive metal and glass. The description of conductive metal and glass is the same as above, so repeated description will be omitted. In addition, the paste for forming the sintered metal film may selectively include adhesive, solvent, dispersant, plasticizer, oxide powder, etc. The adhesive may include, for example, ethyl cellulose, acryl, butyral, etc., and the solvent may include an organic solvent or an aqueous solvent, such as terpineol, butyl carbitol, alcohol, methyl ethyl ketone, acetone, and toluene.

[0149] Methods of applying the paste for forming the sintered metal film to the outer surface of the capacitor body 110 include a dipping method and various printing methods such as a screen printing method, a coating method using a dispenser or the like, and a spraying method using spraying. The paste for forming the sintered metal film is applied to at least the third and fourth sides of the capacitor body 110, and optionally, also to a portion of at least one of the first, second, fifth, and sixth sides of the band portion forming the first external electrode and the band portion of the second external electrode.

[0150] The capacitor body 110 coated with the paste for forming a sintered metal film is dried and sintered at a temperature of 700° C. to 1000° C. for 0.1 to 3 hours to form a sintered metal film.

[0151] Alternatively, the conductive resin layer may be formed by applying a paste for forming the conductive resin layer to the outer surface of the obtained capacitor body 110 and then curing it.

[0152] The paste for forming the conductive resin layer may include resin, and optionally include conductive metal or non-conductive filler. The description of conductive metal and resin is the same as above, so repeated description will be omitted. In addition, the paste for forming the conductive resin layer may optionally include adhesive, solvent, dispersant, plasticizer, oxide powder, etc. The adhesive may use, for example, ethyl cellulose, acryl, butyral, etc., and the solvent may use an organic solvent or an aqueous solvent, such as terpineol, butyl carbitol, alcohol, methyl ethyl ketone, acetone, and toluene.

[0153] As an example, the method for forming the conductive resin layer is to form the conductive resin layer by immersing the capacitor body 110 in a paste for forming the conductive resin layer and then curing it, or by printing the paste for forming the conductive resin layer onto the surface of the capacitor body 110 using a screen printing method or a gravure printing method, or by applying the paste for forming the conductive resin layer to the surface of the capacitor body 110 and then curing it.

[0154] A plating layer is formed on the outer side of the conductive resin layer.

[0155] As an example, the plated layer may be formed by a plating method, or may be formed by sputtering or electrodeposition.

[0156] The above implementation will be described in detail by the following examples. However, the following examples are only for illustrative purposes and are not intended to limit the scope.

[0157] (Manufacturing of multilayer ceramic capacitors)

[0158] Examples 1 to 7 and Comparative Examples 1 to 6

[0159] By mixing BaCO 3 Powder and TiO2 Powder (based on 1 mol of TiO 2 , 0.995 mol parts of BaCO 3 ) prepares a barium titanate main component powder (i.e., a barium titanate-based main component powder), and mixes the barium titanate main component powder and phosphorus pentoxide (P 2 O 5 ) are mixed together. At this time, based on 100 mol parts of the barium titanate main component powder, phosphorus pentoxide (P pentoxide) is mixed in the content shown in Table 1. 2 O 5 ). This was wet mixed with water using a bead mill. The mixture obtained by mixing was dried, and the integrated mixture was dry ground. The pulverized material obtained by dry grinding was calcined at 950° C. for 3 hours under normal pressure. The calcined material obtained by calcination was wet ground, the obtained pulverized material was dried, and dry ground to prepare a dielectric powder.

[0160] The dielectric powder produced and the dielectric powder including dysprosium oxide (Dy 2 O 3 ), terbium oxide (Tb 2 O 3 ), manganese oxide (MnO 2 ), vanadium oxide (V 2 O 5 ), barium carbonate (BaCO 3 ), silicon dioxide (SiO 2 ), aluminum oxide (Al 2 O 3 ) and calcium carbonate (CaCO 3 ) were mixed in the contents shown in Table 1 to prepare dielectric slurry. At this time, each of the subcomponent powders was mixed in a content based on 100 parts by mole of the barium titanate main component powder. 2 Ethanol / toluene (a kind of dispersion medium), a wetting and dispersing agent, and a polyvinyl butyral (PVB) resin as a binder are added together and mechanically ground to produce a mixture.

[0161] A dielectric green sheet was manufactured from the manufactured dielectric slurry using a roll-up coater of a die-discharging type.

[0162] A conductive paste layer including nickel (Ni) was printed on the surface of the dielectric green sheet, and the dielectric green sheets (length×width×thickness=3.2 mm×2.5 mm×2.5 mm) on which the conductive paste layer was formed were stacked and pressed to manufacture a dielectric green sheet stack structure.

[0163] The dielectric green sheet stack is subjected to a degreasing process in a nitrogen atmosphere at 400°C or lower and sintered at a temperature of 1300°C or lower in a hydrogen atmosphere (H 2) concentration is 1.0% or less.

[0164] The external electrodes are formed by a process such as plating to manufacture a multilayer ceramic capacitor.

[0165] Table 1

[0166]

[0167]

[0168] * The molar parts of the corresponding elements based on 100 molar parts of the barium titanate main component powder.

[0169] Assessment 1: ICP analysis

[0170] Inductively coupled plasma (ICP) analysis was performed on the dielectric layers of the multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 to confirm the content of phosphorus (P) element in the dielectric layers. The results are shown in Table 2.

[0171] ICP analysis was performed in the following manner: ten multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were prepared respectively, and the dielectric layers of the prepared multilayer ceramic capacitors were measured by using an AVIO500 (Perkin Elmer) inductively coupled plasma-optical emission spectrometer (ICP-OES) in a quartz chamber under conditions such as a plasma gas flow of 12 L / min, an auxiliary gas flow of 0.2 L / min, a nebulizer flow of 0.5 L / min, a plasma RF power of 1400 W and an axial plasma mode.

[0172] In Table 2, the content of element phosphorus (P) is shown relative to 100 parts by mole of the barium titanate-based main component in the dielectric layer, and the maximum value, the minimum value, and the average value thereof are shown.

[0173] Table 2

[0174]

[0175] *The content of P is the molar part based on 100 molar parts of the barium titanate-based main component.

[0176] The results in Table 2 confirm that in the multilayer ceramic capacitor according to the present embodiment, for Examples 1 to 7, the phosphorus (P) element was included in the dielectric layer in an amount of 0.006 to 0.23 parts by mole based on 100 parts by mole of the barium titanate-based main component.

[0177] Assessment 2: SEM analysis

[0178] The multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were subjected to scanning electron microscope (SEM) analysis, thereby confirming the size and distribution of dielectric grains in the dielectric layer. The results are shown in Table 3.

[0179] SEM analysis was performed as follows. The multilayer ceramic capacitor 100 was placed in an epoxy resin mixed solution and cured, and one side (WT side) of the capacitor body 110 in the W-axis direction and the T-axis direction was polished to 1 / 2 point in the L-axis direction to obtain a cross-sectional sample, which was fixed in a chamber and kept under a vacuum atmosphere, and the effective part including the dielectric layer 111 and the inner electrode layers 121 and 122 was observed. The effective part of the cross-sectional sample was ion milled and measured using SEM. The SEM used a Verios G4 product from Thermofisher Scientific, and the measurement conditions were 10kV, 0.2nA, and an analysis magnification of 100 times.

[0180] The maximum long axes of 100 dielectric grains are measured in the SEM image of the measured cross-sectional sample, a size distribution cumulative curve is generated, and the D10 diameter, D50 diameter, and D90 diameter of the dielectric grains are calculated respectively. At this time, the D10 diameter, D50 diameter, and D90 diameter represent the sizes at the 10%, 50%, and 90% points in the size distribution cumulative curve, respectively.

[0181] In Table 3, the coefficient of variation (CV) of the size of the dielectric grains is calculated by Equation 1.

[0182] [Formula 1]

[0183] Coefficient of dimensional variation (%) = [standard deviation of dimension (σ) / average value] × 100%

[0184] (Here, the standard deviation (σ) of the dimension is the square root of the average value of the square of the deviation, and can be calculated according to the above-mentioned formula 2.)

[0185] Table 3

[0186]

[0187]

[0188] As shown in Table 3, for Examples 1 to 7 including 0.006 mol parts to 0.23 mol parts (based on 100 mol parts of the main component of barium titanate) of phosphorus (P) element in the dielectric layer, the size variation coefficient of the dielectric grains showed lower than that of Comparative Examples 1 to 6. These results show that the multilayer ceramic capacitor according to the present embodiment has dielectric grains uniformly present in the dielectric layer.

[0189] Evaluation 3: Withstand voltage characteristics

[0190] The breakdown voltages (BDVs) of the multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were measured and the results are shown in Table 4.

[0191] Regarding the breakdown voltage (BDV), 50 multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were prepared, respectively, and a voltage was applied from 0 V to 1100 V at every 1.00000 V according to a scanning method using a 2410-type Keithley measuring device, and the voltage value when the current value became 20 mA was measured as the breakdown voltage value. The breakdown voltage was measured in a silicone oil bath.

[0192] Table 4 shows the minimum and average values ​​of the measured BDV and the BDV dispersion. The BDV dispersion was calculated as shown in Formula 3.

[0193] [Formula 3]

[0194] Dispersion (%) = [standard deviation / average value] × 100%

[0195] (Here, the standard deviation is the square root of the average of the squares of the deviations (differences of individual measurements from the mean).)

[0196] Table 4

[0197]

[0198]

[0199] From the results of Table 4, it was confirmed that in the case of Examples 1 to 7 in which the phosphorus (P) element in an amount of 0.006 mol parts to 0.23 mol parts (based on 100 mol parts of the main component of barium titanate) was included in the dielectric layer, the breakdown voltage was high and the dispersion was low, and thus the withstand voltage characteristics were excellent. On the other hand, it was confirmed that in the case of Comparative Examples 1 and 2, the breakdown voltage was low and the dispersion was also high compared with the case of Examples 1 to 7, and in the case of Comparative Example 6, the breakdown voltage was low. In addition, it was found that the withstand voltage characteristics were excellent in the case of Comparative Examples 3 to 5, but as shown in Evaluation 4 described later, the high temperature resistance reliability and the moisture resistance reliability were deteriorated.

[0200] Assessment 4: Reliability

[0201] The multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were measured for highly accelerated life test (HALT) and moisture resistance reliability, and the results are shown in Table 5.

[0202] Specifically, 40 multilayer ceramic capacitors manufactured in Examples 1 to 7 and Comparative Examples 1 to 6 were prepared and mounted on a measurement substrate, and the HALT was measured using an ESPEC (PV-222, HALT) device under the conditions of 150°C, 150 hours and 100 V, and the moisture resistance reliability was measured using an ESPEC (PR-3J, 8585) device under the conditions of 85°C, 85% relative humidity (RH), 32 V and 24 hours.

[0203] Table 5

[0204]

[0205]

[0206] From the results of Table 5, it is confirmed that in the case of Examples 1 to 7 including 0.006 mol parts to 0.23 mol parts (based on 100 mol parts of the barium titanate main component) of the phosphorus (P) element in the dielectric layer, HALT and moisture resistance reliability are excellent compared with Comparative Examples 1 to 6.

[0207] While the present disclosure has been described in conjunction with exemplary embodiments, it should be understood that the present disclosure is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalents included within the spirit and scope of the appended claims.

Claims

1. A multilayer ceramic capacitor comprising: a capacitor body including a dielectric layer and an inner electrode layer; as well as An outer electrode is arranged outside the capacitor body, wherein the dielectric layer comprises a barium titanate-based main component and phosphorus, and Phosphorus is included in an amount of 0.006 parts by mol to 0.23 parts by mol based on 100 parts by mol of the barium titanate-based main component.

2. The multilayer ceramic capacitor according to claim 1, wherein The dielectric layer includes a plurality of dielectric grains, and The dielectric grains include the barium titanate-based main component and phosphorus.

3. The multilayer ceramic capacitor according to claim 2, wherein: The D10 diameter of the dielectric grains is 100 nm to 140 nm.

4. The multilayer ceramic capacitor according to claim 2, wherein: The D50 diameter of the dielectric grains is 150 nm to 250 nm.

5. The multilayer ceramic capacitor according to claim 2, wherein: The D90 diameter of the dielectric grains is 300 nm to 420 nm.

6. The multilayer ceramic capacitor according to claim 2, wherein: The coefficient of variation of the size of the dielectric grains obtained by Formula 1 is 30% to 45%: [Formula 1] Coefficient of variation of size = [standard deviation of size / average value] × 100% In Formula 1, the standard deviation of a dimension is the square root of the average of the squares of the deviations.

7. The multilayer ceramic capacitor according to claim 1, wherein: The dielectric layer further includes a secondary component, and The subcomponent includes at least one selected from the group consisting of dysprosium, terbium, manganese, vanadium, barium, silicon, aluminum, calcium, and combinations thereof.

8. The multilayer ceramic capacitor according to claim 7, wherein: The dielectric layer includes at least one selected from the group consisting of: 0.1 to 1.0 mole parts of dysprosium, 0.1 to 1.0 mole parts of terbium, Manganese in an amount of 0.01 to 0.5 parts by mole, 0.01 to 0.5 mole parts of vanadium, 0.5 to 3.0 parts by mole of barium, Silicon in an amount of 0.5 to 4.0 parts by mole, Aluminum in an amount of 0.1 to 1.0 parts by mole, and Calcium in an amount of 0.01 to 1.0 parts by mole.

9. A method for manufacturing a multilayer ceramic capacitor, comprising: manufacturing a dielectric powder by mixing a barium titanate-based main component powder including a barium precursor and a titanium precursor and a phosphorus-containing compound; manufacturing a dielectric green sheet by using a dielectric slurry including the dielectric powder, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet stack structure by stacking the dielectric green sheets on which the conductive paste layers are formed; manufacturing a capacitor body including a dielectric layer and an internal electrode layer by sintering the dielectric green sheet stack structure; and forming external electrodes on the capacitor body, wherein, based on 100 parts by mole of the barium titanate-based main component powder, a phosphorus-containing compound is mixed in an amount of 0.006 parts by mole to 0.23 parts by mole, and The dielectric layer includes a barium titanate-based main component and phosphorus.

10. The method according to claim 9, wherein: The phosphorus-containing compound includes at least one selected from the group consisting of P2O5, H3PO4, POCl3, phosphorus-containing hydrocarbons, and combinations thereof.

11. The method according to claim 10, wherein: The phosphorus-containing hydrocarbon compound includes at least one selected from the group consisting of a phosphate compound, a phosphite compound, a phosphonate compound, a phosphinate compound, and a combination thereof.

12. The method according to claim 9, wherein: The manufacturing of the dielectric powder further includes, after mixing the barium titanate-based main component powder with the phosphorus-containing compound to prepare a mixture, drying and dry grinding the mixture obtained by mixing, The pulverized material obtained by dry grinding is calcined.

13. The method according to claim 12, wherein: The manufacturing of dielectric powder further comprises: after calcining the crushed material, Wet grinding of the calcined material obtained by calcination, and The pulverized material obtained by wet grinding is dried and dry-milled.

14. The method according to claim 12 or 13, wherein: Calcination is performed at a temperature of 800°C to 1000°C.

15. The method according to claim 9, wherein: The dielectric slurry further includes a secondary component powder, and The auxiliary component powder includes at least one selected from the group consisting of Dy2O3, Tb2O3, MnO2, (V2O5, BaCO3, SiO2, Al2O3, CaCO3 and combinations thereof.

16. The method according to claim 15, wherein: The sub-component powder includes at least one selected from the group consisting of: based on 100 parts by mole of the barium titanate-based main component powder: 0.1 to 1.0 mol parts of Dy2O3, 0.1 to 1.0 mol parts of Tb2O3, 0.01 to 0.5 mol parts of MnO2, 0.01 to 0.5 mole parts of V2O5, 0.5 to 3.0 mole parts of BaCO3, 0.5 to 4.0 mole parts of SiO2, 0.1 to 1.0 mole parts of Al2O3, and CaCO3 in an amount of 0.01 to 1.0 mole parts.